Cooperative Strategic Entrepreneurship: A Case Study from Indonesia - Riza Chakim, Mochamad Heru; Maulina, Erna; Purnomo, Margo; Muftiadi, Anang; Qosasi, Achsanul (International Journal of Criminology and Sociology, 2021)
This article offers an in-depth case study of the relevance of dairy cow milk cooperatives in Indonesia that align with the concept of strategic entrepreneurship in social benefit practices. An advocacy lens based on the strategic entrepreneurship model is used by making comparisons of the constructs that form strategic entrepreneurship to bridge a practical understanding of cooperatives with local cultural backgrounds. Descriptive analysis is used to report interrelated themes in the case study of cooperative organizations and finally interpretation. An interesting finding is based on the research results, that is, the wealth creation of an organization is not the final model variable, but a social benefit variable, which then becomes a cycle of environmental resources. Cooperatives realize that personal benefits are not a sub-variable of constructing goals. This research describes the dynamics of the opening of the concept of strategic entrepreneurship in cooperative companies that consider new social risks and benefits.